BUYING PATTERNS OF VISITORS TOWARDS HANDICRAFT THROUGHOUT SARAWAK REGATTA - Marcini, Ramlie; Shaik Azahar, Shaik Hussain
This research is about the buying patterns of visitors towards handicraft throughtout Sarawak Regatta. Researcher focuses on three objectives which is to identify visitor perceptions of handicrafts, to study the factors that influence visitors in making decisions to buy handicrafts and to analyze visitors' views of handicraft throughout Sarawak Regatta. The method used for this study was quantitative methods by distributing questionnaires to visitors at Waterfront, Kuching. As a result, the motifs or patterns of handicraft throughout Sarawak Regatta attracted visitors. In conclusion, this study is very useful as a reference for handicraft entrepreneurs and future researchers.